1977
DOI: 10.1002/1097-0142(197701)39:1<62::aid-cncr2820390112>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin cardiotoxicity in children.Case reports, literature review, and risk factors

Abstract: Two children with Wilms' tomor and prior thoracic radiation developed congestive heart failure at cumulative adriamycin doses of 350 mg/m2 and 400 mg/m2. Details of these two cases and a summary of previously reported adriamycin cardiotoxicity in children are presented. Dose recommendations and predictive tests are discussed.Cancer 39:62-65. 1977. DRIAMYCIN IS AN ANTINEOPLASTIC AGENTA with a broad range of clinical activity including many childhood neoplasms. Because it may produce long-term remissions in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…It is noteworthy, however, that he had received thoracic irradiation three years previously. Several investigators have reported enhancement of anthracycline cardiotoxicity by thoracic irradiation [3,[15][16][17] and their results are consistent with studies in rabbits demonstrating synergism between the cardiotoxic effects of radiation and adriamycin [18] . Radiation injury tokyocardial capillaries may augment the adriamycin-induced damage to the myofibrils, the sarcoplasmic reticulum and mitochrondia [15] .…”
Section: Discussionsupporting
confidence: 78%
“…It is noteworthy, however, that he had received thoracic irradiation three years previously. Several investigators have reported enhancement of anthracycline cardiotoxicity by thoracic irradiation [3,[15][16][17] and their results are consistent with studies in rabbits demonstrating synergism between the cardiotoxic effects of radiation and adriamycin [18] . Radiation injury tokyocardial capillaries may augment the adriamycin-induced damage to the myofibrils, the sarcoplasmic reticulum and mitochrondia [15] .…”
Section: Discussionsupporting
confidence: 78%
“…These include the degree of anthracycline exposure (high-dose anthracycline infusion or higher cumulative doses are responsible for more frequent cardiac problems), age (the elderly and very young patients have greater risks), a history of cardiac disease, previous cancer therapies (e.g. mediastinal radiation therapy), and the concurrent use of chemotherapy regimens that include paclitaxel or trastuzumab [4][5][6][7].…”
mentioning
confidence: 99%
“…These include radiation of the mediastinum [14, 15], previous cardiac abnormalities, including involvement of the heart by the tumor [16, 17], uncontrolled hypertension [11, 12], and exposure to other chemotherapy modalities such as cyclophosphamide, dactinomycin, mitomycin, vincristine, bleomycin and methotrexate [13, 18, 19]. Demographic factors include young age, female sex, black race and also trisomy 21 [7].…”
Section: Discussionmentioning
confidence: 99%